2019
DOI: 10.1073/pnas.1813504116
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB activation is a turn on for vaccinia virus phosphoprotein A49 to turn off NF-κB activation

Abstract: Vaccinia virus protein A49 inhibits NF-κB activation by molecular mimicry and has a motif near the N terminus that is conserved in IκBα, β-catenin, HIV Vpu, and some other proteins. This motif contains two serines, and for IκBα and β-catenin, phosphorylation of these serines enables recognition by the E3 ubiquitin ligase β-TrCP. Binding of IκBα and β-catenin by β-TrCP causes their ubiquitylation and thereafter proteasome-mediated degradation. In contrast, HIV Vpu and VACV A49 are not degraded. This paper shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 41 publications
2
39
0
Order By: Relevance
“…Substrates of SCF b-TrCP ubiquitin ligase in other cellular processes SCF b-TrCP ubiquitin ligase plays a fundamental role in regulating the activities of multiple biological processes by targeting a range of cellular substrates for ubiquitination and degradation: (a) regulating cellular apoptosis through targeting BimEL [84], MAP3K5/ASK1 [85], MCL1 [86,87], and Pro-caspase-3 [88] for degradation; (b) involvement in virus infection by degrading A49 [89], BST-2 [90,91] (Fig. 4).…”
Section: Substrates Of Scf B-trcp Ubiquitin Ligase In Immunitymentioning
confidence: 99%
“…Substrates of SCF b-TrCP ubiquitin ligase in other cellular processes SCF b-TrCP ubiquitin ligase plays a fundamental role in regulating the activities of multiple biological processes by targeting a range of cellular substrates for ubiquitination and degradation: (a) regulating cellular apoptosis through targeting BimEL [84], MAP3K5/ASK1 [85], MCL1 [86,87], and Pro-caspase-3 [88] for degradation; (b) involvement in virus infection by degrading A49 [89], BST-2 [90,91] (Fig. 4).…”
Section: Substrates Of Scf B-trcp Ubiquitin Ligase In Immunitymentioning
confidence: 99%
“…Using this mechanism A49 binds tightly to β-TrCP only when IKKβ is activated and canonical β-TrCP targets including IκBα and β-catenin accumulate in their phosphorylated forms and are not processed (33,150,151). A49 antagonism of NF-κB contributes to virulence (33,34), but mutant A49 viruses unable to bind β-TrCP retain some degree of virulence suggesting the existence of other β-TrCP-independent functions, perhaps mediated by a second product identified in the A49 ORF (34,152). In addition to these proteins, several VACV proteins including K1 and A55 have been shown to act at the level of the NF-κB heterodimer preventing their translocation or their normal processing (35,43,153).…”
Section: Downstream Nf-κb Inhibitorsmentioning
confidence: 99%
“…Recently, further insight to the mechanism of action of A49 showed that phosphorylation of S7 was necessary for A49 to bind β-TrCP and inhibit activation of NF-κB, whereas S12 was dispensable for these functions [ 8 ]. Therefore, A49 is a conditional inhibitor of NF-κB and requires activation by phosphorylation to become an inhibitor of this pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, A49 is activated to become an inhibitor of NF-κB when the pathway leading to NF-κB activation is switched on. In other words, NF-κB activation is a turn on for A49 to turn off NF-κB activation [ 8 ]. This report also showed that A49 has a second function that contributes to virulence, independent of NF-κB inhibition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation